Chemical Composition of Essential Oil from Rosmarinus Officinalis L. Leaves - Aslı Sönmez; Ayşenur Öz; Burcu Yurdakul; Deniz Gülümser; Mahfuz Elmastas; Necla Türkmen; Ömer Kayır; Ramazan Erenler; Tuğçe Erol (Journal of New Results in Science)
– The chemical constituents of the essential oil from leaves of Rosmarinus officinalis L. was produced by steam distillation using the Clevenger apparatus. The oil was analyzed by gas chromatography and mass spectrometry (GC-MS). The main constituent of the oil was 1,8-cineole with 81.47% which is important for medicinal and pharmaceutical